Formation Mechanisms and Source Apportionments of Nitrate Aerosols in a Megacity of Eastern China Based On Multiple Isotope Observations. Issue 6 (13th March 2023) - Fan, Mei‐Yi; Zhang, Wenqi; Zhang, Yan‐Lin; Li, Jianghanyang; Fang, Huan; Cao, Fang; Yan, Ming; Hong, Yihang; Guo, Hai; Michalski, Greg
Abstract: Inorganic nitrate (NO3 − ) is a crucial component of fine particulate matter (PM2.5 ) in haze events in China. Understanding the formation mechanisms of nitrate and the sources of NO x was critical to control the air pollution. In this study, measurements of multiple isotope compositions of nitrate (δ 18 O‐NO3 −, δ 17 O‐NO3 −, and δ 15 N‐NO3 − ) in PM2.5 were conducted in Hangzhou from 9 October 2015 to 24 August 2016. Our results showed that oxygen anomaly of nitrate (Δ 17 O‐NO3 − : 20.0‰–37.9‰) and nitrogen isotope of nitrate (δ 15 N‐NO3 − : −2.9‰ to 18.1‰) values were higher in winter and lower in summer. Based on Δ 17 O‐NO3 − observation and a Bayesian model, NO3 radical chemistry was found to dominate the nitrate formation in winter, while photochemical reaction (NO2 + OH) was the main pathway in summer. After considering the nitrogen isotopic fractionation in the NO x (g) ‐NO3 − (p) conversion, the average contributions of coal combustion, vehicle exhausts, biomass burning, and soil emission were 50% ± 9%, 19% ± 12%, 26% ± 15%, and 5% ± 4%, respectively, to nitrate aerosols during the whole sampling period. Coal combustion was the most important nitrate source in Hangzhou, especially in winter (∼56%). The contribution of soil emission increased significantly in summer due to active soil microbial processes under high temperature environment. Plain Language Summary: Inorganic nitrate is a crucial component of fine particulate matter in haze events in China. Understanding the formation mechanisms and sources of nitrate was critical to control the air pollution. In this study, measurements of multiple isotope compositions of nitrate showed that oxygen anomaly and nitrogen isotope of nitrate are distinct in winter and summer. Then, nitrate radical chemistry was found to dominate the nitrate formation in winter, while photochemical reaction (nitrogen dioxide with hydroxyl radical) was the main pathway in summer. After considering the nitrogen isotopic fractionation in the conversion from nitrogen oxides to nitrate particle, coal combustion was the most important nitrate source in Hangzhou, especially in winter (56%) and the contribution of soil emission increased significantly in summer under high temperature environment. Key Points: NO3 radical chemistry was dominant in nitrate production in the polluted atmosphere in Hangzhou The isotopic fractionation effect in the NO x (g) ‐NO3 − (p) conversion showed a greater impact on the source apportionment of nitrate aerosols Coal combustion was the main source of nitrate aerosols in Hangzhou